Reduction of regulatory risk: a network economic approach - Günter Knieps; Hans-Jörg Weiß (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2007)
Several definitions of regulatory risk are known from the literature. From the perspective of regulatory reform it is important to differentiate between the impact of a given regulatory scheme on the firm's risk exposure and the risk arising from discretionary behavior of regulatory agencies. Whereas the conse-quences of effective regulation in principle are known and accepted, excessive regulatory discretion may cause a strong need for regulatory reform. Regulatory reform focussing on the regulatory base risk and the regulatory instrument risk has to solve the problem of the optimal division of labour between regulatory discretion and statutory constraints. Therefore, in this paper the design of a disaggregated regulatory mandate is elaborated; its major elements being the restriction of regulation to monopolistic bottlenecks and a disaggregated appli-cation of sector-specific regulatory instruments.
Keywords: 330; Regulierung; Risiko; Netzzugang; Bottleneck